2012
DOI: 10.1111/j.1600-6143.2012.04155.x
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline Level Is a Potent Indicator of Acute Rejection in the Long Term Following Pediatric Intestinal/Multivisceral Transplantation

Abstract: Citrulline has been advocated as a marker for acute cellular rejection (ACR) in intestinal transplantation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 39 publications
0
21
0
2
Order By: Relevance
“…7 Serum citrulline has also been considered, however, it has not been shown to predict asymptomatic rejection and also has significant variability between patients. 8 Immune cell function assay (Cylex ImmuKnow – Viracor IBT Laboratories) has been investigated, and while it may be used as an adjunctive diagnostic tool, it cannot replace endoscopy with biopsy. 9 Finally, the newly FDA-apporved Pleximmune™ test (Plexision, Pittsburgh, PA) is designed to predict the risk of acute cellular rejection after pediatric liver or intestine transplantation, but has yet to be utilized in a large multi-center study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Serum citrulline has also been considered, however, it has not been shown to predict asymptomatic rejection and also has significant variability between patients. 8 Immune cell function assay (Cylex ImmuKnow – Viracor IBT Laboratories) has been investigated, and while it may be used as an adjunctive diagnostic tool, it cannot replace endoscopy with biopsy. 9 Finally, the newly FDA-apporved Pleximmune™ test (Plexision, Pittsburgh, PA) is designed to predict the risk of acute cellular rejection after pediatric liver or intestine transplantation, but has yet to be utilized in a large multi-center study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on visual surveillance of intestinal allografts via endoscopic evaluation have concluded that biopsy is mandatory for detecting early, treatable rejection even though visual inspection of grafts is able to detect severe rejection [71]. Serum citrulline and fecal calprotectin have recently emerged as potential reliable noninvasive indicators of acute rejection [72,73]. Furthermore, gut microbiota, proteomics and metabolomics such as pro-inflammatory mediator leukotriene E 4 , vitamins-B 2 , B 5 , B 6 and taurocholate may be able to identify bioprofiles associated with intestinal rejection [74,75].…”
Section: Intestinal Failurementioning
confidence: 99%
“…В то же время разработка систем надежных пока-зателей по результатам исследования крови продол-жается [39][40][41][42][43][44], так как кровь в клиническом плане наиболее доступная и насыщенная информацион-ная среда, а индустрия современной диагностики имеет практически неограниченные возможности, так как позволяют определить в крови концентра-цию практически любой значимой молекулы [41].…”
Section: диагностика доминирующего стереотипа иммунного реагироваunclassified
“…Идеальным вариантом такого маркера может служить недав-но показанная в эксперименте связь концентрации цитрулина в крови и острого или хронического отторжения при интестинальной и мультивисце-ральной пересадке органов [43]. Установлена кри-тическая концентрация цитрулина для острого (10 мкМ/л) и для хронического (20 мкМ/л) отторжения.…”
Section: маркеры метаболизма в трансплантатеunclassified